Clinico-demographic profile and outcome of neonates born to mothers with COVID-19 infection at a Tertiary Care Hospital - Zafar, Farhana; Ehsan, Shaista; Khan, Lubna; Fawad, Bina (Journal of Liaquat University of Medical & Health Sciences, 2023)
Objective: To determine the Clinico-demographic profile and outcome of neonates born to mothers with COVID-19 infection at a Tertiary Care Hospital. Methodology: This cross-sectional study was conducted at Pediatrics Department, Ziauddin Hospital Karachi, from March 2020 to August 2021. The sample size was 31, non-probability purposive sampling technique was used. Neonates of COVID positive mothers who consented to Covid-19 testing were included. Neonates of Covid positive mothers who refused to participate were excluded. Diagnosis of coronavirus infection was based on Novel Corona Virus-2019 (nCoV-19) qualitative PCR test through nasopharyngeal swab. Clinico-demographic profile and outcome of neonates data were recorded on self-developed proforma. Standard protocols were followed per National Command and Operation Center guidelines. Data were analyzed by SPSS version 20. Frequencies and percentages were calculated, and the chi-square test was applied as a significance test with a P-value of <0.05. Results: First virology test was positive for 6 (19.4%) neonates, and the second was positive for only 1 (3.2%) neonate; 17 (54.8%) neonates who were negative in the first virology test and stayed less than three days in the hospital refused to undergo a second test by their parents. After 14 days of follow-up, 29 (93.5%) neonates became asymptomatic, while 2 (6.5%) had symptoms of neonatal respiratory distress and required admission to the neonatal intensive care unit. Conclusion: Vertical transmission of covid-19 can occur if the mother acquires infection in the last trimester. However, these infected neonates’ morbidity and mortality rate is negligible; therefore, breastfeeding and rooming should be encouraged.